Evaluasi Pelaksanaan Pengawasan Barang Milik Daerah Untuk Tertib Administrasi Pada Bagian Perlengkapan Sekretariat Daerah Kota Bekasi - Simamora, Nurcahaya; Irawan, Bambang (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Starting from the background of this study, the supervision of the management of regional property carried out by the Equipment Section so far in the author's observation is still considered ineffective due to various problems found in the use of BMD in several OPDs, sub-districts and sub- districts. Some of these problems include records and findings from the Inspectorate on the use of computers in OPDs that are not in accordance with the standards according to applicable regulations, some official vehicles are not immediately returned after the expiration of their term of office, damage to BMDs without maintenance. This shows that the supervision carried out by the Equipment Section is still considered technically and administratively negligent. This study uses a qualitative descriptive research method with data collection through interviews and observations. The theory used in this study is the supervision theory from Pasaribu (2011) where supervision will run well if there are four key indicators, namely monitoring, examination, guidance, disciplinary action and corrective action. From the results of the research analysis conducted by the researcher, based on this theory, most of the supervision carried out by the Equipment Section is in accordance with the rules, it's just that due to several factors, the supervision does not run less than optimally. However, the Equipment Section continues to strive to overcome these obstacles through the direction and guidance of the leadership